2015
DOI: 10.3991/ijoe.v11i4.4562
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Students Use and Appreciate Online Resources in the Teaching Laboratory

Abstract: Abstract-The internet is a great resource student's use for learning. Reasons include the ease in searching with sites such as Google, or the vast collection of informative videos on YouTube. The teaching laboratory can also benefit from online resources, especially when students are deficient in prerequisite knowledge. The benefits are greatest when there are non-standard learning paths, and multiple entry points into a degree. This study undertakes a mixed methods research approach to try and understand how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…There may be a difference on how they look with the materials and how they view it as a helpful resource in education. Nikolic (2018) finds that such e-learning resources are used by a substantial number of students to aid learning, increasing productivity, and improving teaching. The availability of such targeted resources leads to an improved student experience.…”
Section: Pointmentioning
confidence: 99%
“…There may be a difference on how they look with the materials and how they view it as a helpful resource in education. Nikolic (2018) finds that such e-learning resources are used by a substantial number of students to aid learning, increasing productivity, and improving teaching. The availability of such targeted resources leads to an improved student experience.…”
Section: Pointmentioning
confidence: 99%
“…another Australian university by ensuring females were placed in larger groups, disregarding the need to create diversified groups [4]. As interest, a statistically significant jump occurred in 2017 for males for confidence in upcoming challenges.…”
Section: Nomentioning
confidence: 99%
“…Some reasons include providing all students a pathway to fields most likely to dominate future employment, ensuring growth targets can be met, and that innovations will be better targeted and valued by a greater cross section of society [3]. This is driving research to better understand what attracts students to the field, their transition to higher education and their learning experience [4]. In particular, a focus in research has been to develop a better understanding of female and minority group's motivations and experiences to start and continue an education within a STEM discipline [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that evaluation scores increased by improving communication, classroom management and teaching technique. A few other studies Nikolic 2015;Nikolic 2014) explored how improvements to the laboratory experience, defined by the experiments they undertook and the facilities they used, were correlated to the student evaluation scores. These studies found an intertwined connection between activity, clarity, resources and facilities.…”
Section: Purpose Of Studymentioning
confidence: 99%